URINARY CONTINENCE DIVERSION IN CHILDREN WITH NEUROGENIC BLADDER - Satyawan, Yopie T; Rodjani, Arry; Wahyudi, Irfan (Indonesian Urological Association, 2015)
Objective: We evaluate the initial experience of the implementation of the urinary diversion procedure in patients with neurogenic bladder continence in children. Material & method: The study was conducted retrospectively by collecting data contained in patient medical records of patients who come for treatment to Cipto Mangunkusumo Hospital Jakarta, from 2003 to 2012, and by interviews with parents of patients over the phone or when the patients control to the clinic. The patient is a child (age 0-18 years), diagnosed with congenital neurogenic bladder, and had urinary diversion continence procedure. Results: There are eight cases with urinary diversion continence undertaken in Cipto Mangunkusumo Hospital and found only 7 cases met the inclusion criteria with more girls than boys. Common etiology was spina bifida (57%). Most of the patients complained of recurrent UTI, and the most techniques used are Mitrofanoff (72%) with complications 33%. Conclusion: Urinary diversion continence procedure that has been done in Urology of Cipto Mangunkusumo Hospital is Mitrofanoff-Monti. Of the total of seven cases performed, the initial evaluation gives good results after urinary diversion continence procedure. Improved quality of life of patients with the achievement continence, overcome recurrent UTI problems and kidney function can be retained. Keywords: Neurogenic bladder, Mitrofanoff techniques, Yang-Monti.